The Influence of Brand Halal Awareness and The Halal Logo On Online Food Purchasing Decisions - Maricar, Rezvanny; Mallu, Angga Prayudha Ashari H; Akbar (IJHCM (International Journal of Human Capital Management), 2024)
The purpose of this study is to explore the effects between halal brand awarness and halal logo on online purchasing decisions. Cross-sectional data samples were collected through surveys from consumers living in Indonesia, and this study adopted path analysis to test the hypothesised relationships between halal brand awareness, towards purchase decisions and halal logo towards purchase decisions. This study suggests that food businesses should brand-build and promote their brand awareness of the halal logo through sales promotion, advertising, and other marketing activities. When brand halal awareness on halal food is high, purchasing decisions through the halal logo and religious beliefs will also increase. Consumers will evaluate the quality of a product from the halal food purchase experience.